Alternative therapies - Schachter, Steven (Henry Stewart Talks, 2011)
Complementary and alternative therapies (CAM) in epilepsy, Scope of use of herbs and regulatory aspects, Standards set forth by the DSHEA, Quality control issues, Unmet medical needs, Epilepsy drug statistics, Why botanicals?, East Asian literature of herbs, FDA guidance, Chemicals in botanical drug products, Harvard epilepsy botanical program, From tradition to bench to bedside